Controversy over the economic justifications for patent protection - Adam Karbowski; Jacek Prokop (Procedia – Economics and Finance. International Conference on Applied Economics (ICOAE) 2013, 2013)
The objective of this paper is to show the necessity of reviving the debate on the economic justifications for patent protection. On the one hand, we see the need for the assessment of the overall welfare consequences of the existing systems of patent protection, and on the other hand, we believe that major changes to the patent law should be considered. Critical review of the discussion on patents shows that the weaknesses of many arguments for patent protection, as well as the resulting adverse effects of the patent laws have been known for a long time. The analysis of the strategic behavior of firms shows that patent protection has often been misused and may negatively affect the total welfare.
Keywords: O32; O34; 330; patents; intellectual property; restrictions on competition; Patent; Intellectual property management